2019
DOI: 10.2135/cropsci2018.05.0323
|View full text |Cite
|
Sign up to set email alerts
|

Activity, Purification, and Analysis of Condensed Tannins: Current State of Affairs and Future Endeavors

Abstract: As a class of plant polyphenolic compounds contained in some forages (i.e., sainfoin [Onobrychis viciifolia Scop.], big trefoil [Lotus pedunculatus Cav.], birdsfoot trefoil [Lotus corniculatus L.]), condensed tannins (CTs), also referred to as proanthocyanidins (PAs or PACs), exhibit a variety of biological effects on ruminants. The potential positive impact of CTs on the agricultural industry stems from their ability to modulate proteolysis during forage conservation and ruminal digestion, to prevent bloat, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 161 publications
(296 reference statements)
1
86
0
2
Order By: Relevance
“…Current thinking suggests that these secondary metabolites provide plants with a plasticity that can support their development and interaction with the environment (Bidel et al, 2010;Neilson et al, 2013;Mouradov and Spangenberg, 2014). It is important to appreciate that a multitude of different CT compounds exist (Khanbabaee and van Ree, 2001;Hümmer and Schreier, 2008;Salminen and Karonen, 2011;Zeller, 2019), and that their synthesis in the plant kingdom has not converged on a single structure. For example, Chen et al (2014) showed that the temperatures experienced by the mother plant elicit CT pathways that can pass information to the next generation.…”
Section: Roles Of Tannins In Plants and Challenges To Harnessing Theimentioning
confidence: 99%
See 3 more Smart Citations
“…Current thinking suggests that these secondary metabolites provide plants with a plasticity that can support their development and interaction with the environment (Bidel et al, 2010;Neilson et al, 2013;Mouradov and Spangenberg, 2014). It is important to appreciate that a multitude of different CT compounds exist (Khanbabaee and van Ree, 2001;Hümmer and Schreier, 2008;Salminen and Karonen, 2011;Zeller, 2019), and that their synthesis in the plant kingdom has not converged on a single structure. For example, Chen et al (2014) showed that the temperatures experienced by the mother plant elicit CT pathways that can pass information to the next generation.…”
Section: Roles Of Tannins In Plants and Challenges To Harnessing Theimentioning
confidence: 99%
“…We emphasize that the widely used elution of plant extracts with 70% aqueous acetone from Sephadex LH-20 columns for tannin "purification" can lead to CT concentrations as low as ~13 g CTs 100 g −1 "purified sample" (Williams et al, 2014b). Thiolysis or phloroglucinolysis (analytical degradation of CTs with thiols or phloroglucinol) can be used to determine the composition of CTs by depolymerization, enabling characterization of the flavan-3-ol subunits (Zeller, 2019). (Gea et al, 2011;Pérez-Jiménez and Lluís Torres 2011;Cheynier et al, 2015;Hixson et al, 2016;our unpublished data).…”
Section: Progress In Tannin Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Wayne Zeller from the US Dairy Forage Research Center in Madison, WI, reported on the activity, purification, and analysis of CT (Zeller, 2019). Wayne Zeller from the US Dairy Forage Research Center in Madison, WI, reported on the activity, purification, and analysis of CT (Zeller, 2019).…”
Section: Abbreviations: Ct Condensed Tannin(s)mentioning
confidence: 99%